Resistance to Adversities in Teenagers, High School Students, and University Students - Sorokoumova, S. N.; Dunaeva, N. I. (Вестник Кемеровского государственного университета, 2022)
This research featured theoretical and practical approaches to resistance. Resistance to adversities is an important personality trait because it determines the strategy of behavior in various situations. Personal resilience requires a multidimensional assessment of personality traits, age profile, and solution strategies. The research objective was to identify and compare the trends in resistance in three age groups: teenagers, high school students, and university students. The authors developed a diagnostic complex to determine its component structure. The article describes behavioral patterns, socio-psychological adaptation, personal value orientations, life-meaning attitudes, and manifestations of subjectivity. The authors plan to design a program for the development of resistance in academic environment.